Effect of Chemical Treatment, Wax Coating, Oil Dipping and Different Wrapping Materials on Physio-chemical Characteristics and Storage Behavior of Apple (Malus domestica Borkh) - Sabir, Syed Mubashir; Shah, Syed Zulfiqar Ali; Afzal, Abida (Pakistan Journal of Nutrition, 2004)
Chemical treatment, wax coating, oil dipping and different wrapping materials have significant role in extending the shelf life of apple. The present investigation was therefore, carried out to extend the shelf life of Banky cultivars of apple by applying the above mentioned treatments. In physical characteristics general appearance (color and shape of fruit), weight loss percentage and organoleptic evaluation were studied during storage. Chemical treatment, total soluble solids, pH, acidity, total sugar, reducing sugar and Vitamin C were analyzed after 15, 30, 45 and 60 days of storage. All the treatment had significant effect on the shelf life of fruits. However, Non-perforated polyethylene was reported superior to all other treatments. Non-perforated polyethylene materials proved very useful for reducing weight loss and shriveling and retained consumer acceptability even after 60 days of storage. Hydroxyquinoline and butter paper wrapping stood second and third positions after non perforated polyethylene wrapping.